Sexual abuse in comparison of canon law of Roman Catholic Church and national criminal law on the example of Slovakia - Blažek, Radovan; Tarabová, Nina (Studia Prawnoustrojowe, 2021)
Lately we are facing the new rules of Roman Catholic Church Law, that are also focused on the sexual abuse of minors and its punishment, announced on June 1st, 2021. These new rules should come into effect on 8 December 2021. This occasion offers a good opportunity for analysis of this specific social problem (sexual abuse) and its punishment from the religious and secular perspectives. Authors offers an example of national law of Slovakia in comparaison with Roman Catholic Church Law and the way how they deal with the problem of sexual abuse. In this paper, we report on the criminal responsibility of pastors and clerics for the sexual abuse in the light of national criminal law and Canon Law. This is significant because the position of pastor could influence also the responsibility according to secular criminal law, and on the other side, the responsibility in criminal law is not only one and the consequences for clerics will appear also in the scope of Canon law. The criminal and Canon Law responsibility exist separately but in this case is important to think how they influence each other.